Early to Late Paleoproterozoic magmatism in NE Brazil: The Alto Moxotó Terrane and its tectonic implications for the Pre-West Gondwana assembly. (March 2015) - Santos, Lauro Cézar Montefalco de Lira; Dantas, Elton Luiz; Santos, Edilton José dos; Santos, Roberto Ventura; Lima, Haroldo Monteiro
Abstract: The Alto Moxotó Terrane is a Paleoproterozoic inlier within the Transversal Domain of the Neoproterozoic Borborema Province (NE Brazil). An isotopic and whole-rock geochemistry study has been performed in the Sucuru region (Paraiba State, NE Brazil) which revealed a long-lived evolution for this terrane. The first event is Siderian-aged, dated on 2.44 Ga, being represented by granitic to granodioritic banded orthogneisses and migmatites of the basement. They correspond to meta to peraluminous high-K calc-alkaline series, where geochemical patterns besides zircon features and Nd isotopic data indicate that they were formed in a convergent tectonic environment with reworking of an older Archean continental crust. This basement was intruded by different magmatic suites through two distinct tectono-magmatic events. The older one is Rhyacian-aged recorded by emplacement of the Carmo mafic-ultramafic suite and Pedra d'Água granitic suite, with ages varying from 2.15 to 2.0 Ga. The Carmo Suite shows compositions similar to tholeiitic and minor calc-alkaline series and geochemical patterns of a depleted source. These general chemical characteristics are compatible with an arc-related magmatism in early stages of subduction. The Pedra d'Água suite corresponds to middle to peraluminous high-K calc-alkaline magmatism which presents a typical magmatic arc geochemical signature. The negative εNd ( t ) values suggest a strong continental component for genesis of these magmas. The last tectonomagmatic episode occurred in the Statherian-Calymmian boundary and is represented by bimodal magmatic association of the Serra da Barra Suite, dated around 1.6 Ga. The dominant felsic rocks present an evolved composition and correspond to typical metaluminous sub-alkaline suite. The trace-element and REE patterns of both mafic and mainly felsic rocks suggest a within-plate setting. The attributed source is of crustal derivation, which is supported by the negative εNd ( t ) values. A mantle plume can be invoked for mechanism of generation of the Serra da Barra magmatism. This polycyclic Paleoproterozoic evolution observed at Alto Moxotó terrane is also well documented in orogenic terranes worldwide, mainly those related to Atlantica supercontinent amalgamation. On the other hand, Statherian-Calymmian extensional event is also coherent with worldwide descriptions and are commonly referred to early break-up stage of the large Paleoproterozoic land masses. Graphical abstract: Highlights: Paleoproterozoic juvenile and crustal growth. Paleoproterozoic accretionary events in NE Brazil. Formation and break-up of continents.